THE RELATIONSHIP BETWEEN WORK ATTITUDE AND LEADERSHIP WITH THE PERFORMANCE OF HEALTH WORKERS AT PUBLIC HEALTH CENTER IN PARIAMAN CITY - Surya, Rezi Fatrima; Lestari, Yuniar; Kasra, Kamal (Politeknik Kesehatan Kemenkes RI Jakarta I, 2024)
The increase in the number of health workers by 26% from the previous year was not in line with the increase in program achievements at the Public Health Center (PHC) in the working area of the Pariaman City Health Office which had not yet reached the set targets such as the target for non-communicable disease services (NCD) which on average only reached 37.31% of the target. This is partly due to the low performance of health workers at the public health center. This study aims to analyze the relationship between work attitudes and leadership with the performance of health workers in the Essential Public Health Efforts (PHE) program at the Pariaman City Health Center. This study is quantitative research with a cross sectional approach. Sampling of this study was carried out by proportional random sampling of 89 respondents from a population of 100 health workers. The results showed that work attitude has a significant relationship with officer performance while leadership does not have a significant relationship with health workers performance. It can be concluded that improving the health workers work attitudes will improve the performance of health workers and improving the leadership of the head of public health center does not improve the performance of the health workers.